1995
DOI: 10.1016/0029-7844(94)00309-2
|View full text |Cite
|
Sign up to set email alerts
|

Instruments & Methods Laparoscopically assisted vaginal removal of ovarian dermoid cysts

Abstract: Dermoid cysts were diagnosed by transvaginal sonography in 19 patients who subsequently underwent laparoscopy to confirm the nature and extent of the lesion and the mobility of the adnexa. Eighteen patients underwent surgery after the ovary was exteriorized through a posterior colpoceliotomy. No intraoperative complications were observed, and sonographic follow-up at 3 and 6 months after surgery showed a normal sonographic ovarian pattern. Laparoscopically assisted vaginal removal of dermoid cysts should be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 3 publications
1
13
0
1
Order By: Relevance
“…In fact the mean operative time in our experience (64 min) is similar to that reported by Volz et al [10], who used a similar technique, and by Yuen and Rogers [20] (60 min) and Morgante et al [58] (57 min) for open surgery and by Pardi et al [42] for laparoscopy-assisted vaginal removal, but it was lower than what was reported by other authors for laparotomy [18,21,22] or laparoscopy (table 2), [8,9,12,18,19,20,21,22,26,27,29,33,34,36,37,39,40]. Our mean surgical time is also lower than that reported by Ferrari et al [38] or Wang et al [44] for the direct vaginal approach (81 and 78 min, respectively).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In fact the mean operative time in our experience (64 min) is similar to that reported by Volz et al [10], who used a similar technique, and by Yuen and Rogers [20] (60 min) and Morgante et al [58] (57 min) for open surgery and by Pardi et al [42] for laparoscopy-assisted vaginal removal, but it was lower than what was reported by other authors for laparotomy [18,21,22] or laparoscopy (table 2), [8,9,12,18,19,20,21,22,26,27,29,33,34,36,37,39,40]. Our mean surgical time is also lower than that reported by Ferrari et al [38] or Wang et al [44] for the direct vaginal approach (81 and 78 min, respectively).…”
Section: Discussionsupporting
confidence: 75%
“…In order to reduce the risk of spillage during laparoscopy, some authors propose to remove dermoid cysts via culdotomy through an incision on the posterior vaginal fornix [26,35,42,43,44], but with this technique Teng et al [31] reported 6 cases of spillage from 14 cysts (43%); Reich et al [26] reported 9 cases of spillage in 25 cysts removed vaginally (36%), and in the experience of Nezhat et al [35] spillage occurred in 4 of 9 cysts (44%). In a retrospective study, Ferrari et al [38] proposed a direct vaginal approach without laparoscopic assistance for surgical treatment of ovarian dermoid cysts.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, the guanosine amino nitrogen assignments were obtained by observation of strong NOEs between adjacent guanosine imino and amino protons . These new techniques for resonance assignment and structure determination, when combined with previously developed techniques (see Pardi (1995) for a review), greatly simplify the assignment and structure determination of isotopically labeled RNAs.…”
Section: Discussionmentioning
confidence: 98%
“…However, the risk of penetration of the large tumors with the introduction of the Veress needle and, subsequently, the trocar has led to the recommendation for insertion of the needle and trocar under sonographic control or the use of open laparoscopy. [10][11][12][13] In our patient, we chose an open laparoscopy. The trocars were inserted under visual control, and controlled decompression was achieved by the insertion of a needle connected to a suction apparatus, secured with a purse-string suture to prevent fluid leakage.…”
Section: Laparoscopic-assisted Vaginal Ovarian Cystectomymentioning
confidence: 98%
“…3,12,14 A review of the English literature on laparoscopicassisted vaginal or vaginal management of ovarian tumors disclosed that the rate of cervical laceration, infection, and conversion to laparotomy were 0.6 (1=168), 6.5 (11=168), and 7.7% (13=168), respectively ( Table 2). [6][7][8][9]11,12 Our study required no open conversion and 1 patient (10.0%) suffered from postoperative infection controlled by 3-day parenteral antibiotic therapy. The complication rate was less than average (10.0 versus 13.8%; Table 2).…”
Section: Laparoscopic-assisted Vaginal Ovarian Cystectomymentioning
confidence: 99%